1972
DOI: 10.1097/00006842-197209000-00002
|View full text |Cite
|
Sign up to set email alerts
|

The Immediate Effects of Systematic Relaxation Training on Peak Expiratory Flow Rates in Asthmatic Children

Abstract: Clinical experience has often suggested that having asthmatic patients sit quietly and/or relax during asthma attacks is helpful. The present study was an attempt to provide a controlled experimental demonstration of the effect of systematic relaxation on peak expiratory flow rate in asthmatic children. Eighteen male and 18 female asthmatic children were divided into two groups matched for mean age, sex composition and asthma severity. One group of subjects underwent three sessions of modified jacobsonian syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 11 publications
1
41
0
2
Order By: Relevance
“…Two studies were published in the 1970s (Alexander, 1972, 363 Davis 382,383 ), eight in the 1980s (Alexander, 1988, 402 Backman, 385 Evans, 403 Gold, 418 Gustafsson, 419,420 McNabb, [412][413][414][415] Mitchell, 376 Westphal 410 ), 16 in the 1990s (Colland, 378 Collins, 407 Dahl, 381 Fisher, 408,409 Garrett, 404 Greineder, ). The breakdown of studies by decade of publication according to the main type of intervention evaluated is shown in Figure 4.…”
Section: Publication Datesmentioning
confidence: 99%
“…Two studies were published in the 1970s (Alexander, 1972, 363 Davis 382,383 ), eight in the 1980s (Alexander, 1988, 402 Backman, 385 Evans, 403 Gold, 418 Gustafsson, 419,420 McNabb, [412][413][414][415] Mitchell, 376 Westphal 410 ), 16 in the 1990s (Colland, 378 Collins, 407 Dahl, 381 Fisher, 408,409 Garrett, 404 Greineder, ). The breakdown of studies by decade of publication according to the main type of intervention evaluated is shown in Figure 4.…”
Section: Publication Datesmentioning
confidence: 99%
“…However, related efficacy studies have shown contradictory results. Occasionally, the effect of muscular relaxation on pulmonary function variables proved to be significant on a statistical level, but its effect has rarely been of clinically significant magnitude [6, 7]. One example of sufficient peripheral relaxation was provided by Glaus and Kotses [8, 9], who found a reliable correlation between facial muscle tension and airway caliber.…”
Section: Introductionmentioning
confidence: 99%
“…The trials used four broad psychological approaches; six studies included an element of relaxation in their intervention [10][11][12][13][14][15][16], two included cognitive behavioural therapy [17,18], and three used biofeedbackassisted relaxation and one behavioural therapy [14,[19][20][21]. Different placebos or controls were used, and rarely was the therapy delivered in its pure form, but, instead, therapists often combined therapies or tailored them to the individual's needs.…”
Section: Psychological Interventions For Children With Asthmamentioning
confidence: 99%
“…Unfortunately, with a total of 22 different outcome measures and the diversity of psychological therapies trialled, only data from two studies of relaxation therapy could be pooled for analysis [10,16]. The meta-analysis demonstrated a positive effect of relaxation therapy on lung function (PEFR) in the intervention group (32 L/min, 95 % CI 13 to 50 L/min).…”
Section: Psychological Interventions For Children With Asthmamentioning
confidence: 99%